Masjid Sebagai Pusat Ibadah dan Pembinaan Keagamaan Masyarakat di Kenagarian Guguak VIII Koto - Habil Hidayatul Rasyad; Sarwan Sarwan; Nora Zulvianti; Fitriani Ayu Lestari (Universitas Islam Negeri Imam Bonjol Padang, 2021)
Seeing the existence of mosques in the present era in a physical sense, the movement in the construction of mosques has developed rapidly, as seen by the fact that many magnificent and modern mosques have been built, especially in Kenagarian Guguak VIII Koto, but the physical construction of mosques is not in accordance with the religious progress of the community. In this regard, one of the mosque administrators revealed that congregational prayer activities are sometimes crowded and sometimes quiet, as well as other religious activities. What was conveyed by him has become common knowledge because Arif Hidayat in the results of his research found that mosque buildings are getting more magnificent but worship activities and spiritual formation are quiet from the congregation. This research is a form of social research that uses a qualitative descriptive format, is research that aims to describe, summarize various conditions, as situations or various social reality phenomena that exist in the society that are the object of research, and try to draw that reality to the surface as a characteristic, character. , properties, models, signs, or descriptions of certain conditions, situations or phenomena. The board has made a lot of effort in making the mosque a center of worship, such as maximizing the facilities and infrastructure of the mosque to make it comfortable to use. However, there has been no satisfactory result because the number of people who come is small.Keyword : Mosques, Religious, Management